Comparison of Intradermal Dexmedmotidine and Subcutaneous Ketamine for Post-surgical Pain Management in Patients with Abdominal Hysterectomy - Alireza Kamali; Maryam Shokrpour; Zahra Zarepour; Shirin Pazuki (PAGEPress Publications, 2019)
Hysterectomy after cesarean section is the second most commonly used surgery for women in the United States. One of the most common problem after hysterectomy is pain. We decided to compare the effects of dexmedmotidine or ketamine on pain in patients by a double blind randomized clinical trial on 126 female candidates for abdominal hysterectomy in three groups of 42 persons referred to Taleghani hospital in Arak. For the first group, 50 micrograms of intradermal dexmedmotidine were injected, while in the second group, patients were injected with 100 mg of subcutaneous ketamine and the third group received 5 cc normal saline. Data were next analyzed by SPSS version 19. The mean age and body mass index of the patients were not significantly different in the three groups. The mean scores of pain during recovery of patients in ketamine, dexmedmotidine and placebo groups were 4.2±0.77, 2.6±0.89 and 1.3±0.87, respectively (p = 0.001). Scores of pain in patients at 4 and 8 hours after surgery showed also significant differences. In conclusion, ketamine and dexmedmotidine significantly reduce the severity of pain, but ketamine has a lower effect.